2012
DOI: 10.1182/blood-2011-08-376038
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant lectin-like domain of thrombomodulin inhibits angiogenesis through interaction with Lewis Y antigen

Abstract: IntroductionAngiogenesis is involved in physiologic processes such as embryogenesis, wound healing, and the female reproductive cycle, and also contributes to the pathogenesis of numerous disorders, including atherosclerosis, ischemic disease, arthritis, and cancer. 1 Normally, angiogenesis is strictly controlled by the balance between angiogenic promoters and inhibitors.Thrombomodulin (TM) is a type I-glycosylated membrane protein composed of 5 distinct domains. At the NH 2 -terminal is a C-type lectin-like d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
5
36
2
Order By: Relevance
“…However, studies by our team [13] and others [14] have shown that THBD also has a protein C-and thrombinindependent physiological function. In agreement with this notion, we recently demonstrated that recombinant THBDD1 (rTHBDD1 ) can inhibit an inflammatory response by neutralising lipopolysaccharide through binding to Lewis Y antigen [15] and has anti-angiogenesis effects on cultured HUVECS [16]. We also demonstrated that cardiomyocytes are protected from apoptosis by THBD treatment as a result of its effect on the balance of B cell leukaemia/lymphoma 2 (BCL-2) and BCL-2-associated X protein (BAX) levels [17].…”
supporting
confidence: 48%
See 3 more Smart Citations
“…However, studies by our team [13] and others [14] have shown that THBD also has a protein C-and thrombinindependent physiological function. In agreement with this notion, we recently demonstrated that recombinant THBDD1 (rTHBDD1 ) can inhibit an inflammatory response by neutralising lipopolysaccharide through binding to Lewis Y antigen [15] and has anti-angiogenesis effects on cultured HUVECS [16]. We also demonstrated that cardiomyocytes are protected from apoptosis by THBD treatment as a result of its effect on the balance of B cell leukaemia/lymphoma 2 (BCL-2) and BCL-2-associated X protein (BAX) levels [17].…”
supporting
confidence: 48%
“…In a recent study, we showed that administration of AAV serotype 2/8 carrying THBDD1, which was also used in the present study, can cause hepatic expression of THBDD1 and release of the protein into blood, thereby inhibiting angiogenesis in rats [16]. Other authors [23] have shown that recombinant AAV serotype 2/8 vectors are a promising tool for long-term tissue protein expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 On the other hand, TMD1 inhibited angiogenesis through interaction with Lewis Y antigen. 28 TMD1 dephosphorylated ERK and decreased levels of Mcl-1 in HUVECs ( Figure 6D). TMD1 possesses the distinct function in endothelial cells from other domains of TM.…”
Section: Discussionmentioning
confidence: 99%